1988
DOI: 10.1002/1097-0142(19881215)62:12<2507::aid-cncr2820621210>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Management of stage III primary breast cancer with primary chemotherapy, surgery, and radiation therapy

Abstract: One hundred seventy-four evaluable patients with noninflammatory Stage III (both operable and inoperable) breast cancer were treated with a combined modality strategy between 1974 and 1985. All patients received combination chemotherapy with 5-fluorouracil, Adriamycin (doxorubicin), and cyclophosphamide (FAC) as their initial form of therapy. After three cycles of chemotherapy, local treatment in the form of a total mastectomy with axillary dissection, or radiotherapy, or both, was completed. Subsequently, adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
168
2
14

Year Published

1991
1991
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 467 publications
(196 citation statements)
references
References 20 publications
(2 reference statements)
9
168
2
14
Order By: Relevance
“…patients with ER-poor or ER-negative tumours). The proportion of such patients with tumours which were chemosensitive was high and lies within the observed range of 70-93% described with 'neoadjuvant' chemotherapy in more locally advanced breast cancers (Jacquillat et al, 1988;Hortobagyi et al, 1988;Swain et al, 1987). Of those individual tumours directly demonstrated as endocrine-resistant however the proportion of ER-poor/ negative tumours regressing with chemotherapy paralleled that of primary chemotherapy (-80%) In addition to the benefit of selecting appropriate systemic therapy, there is theoretical (Goldie & Coldman, 1979;Skipper 1964), experimental (Fisher et al, 1983) and clinical (Nissen-Meyer et al, 1986;Ragaz, 1986) …”
Section: Resultssupporting
confidence: 63%
“…patients with ER-poor or ER-negative tumours). The proportion of such patients with tumours which were chemosensitive was high and lies within the observed range of 70-93% described with 'neoadjuvant' chemotherapy in more locally advanced breast cancers (Jacquillat et al, 1988;Hortobagyi et al, 1988;Swain et al, 1987). Of those individual tumours directly demonstrated as endocrine-resistant however the proportion of ER-poor/ negative tumours regressing with chemotherapy paralleled that of primary chemotherapy (-80%) In addition to the benefit of selecting appropriate systemic therapy, there is theoretical (Goldie & Coldman, 1979;Skipper 1964), experimental (Fisher et al, 1983) and clinical (Nissen-Meyer et al, 1986;Ragaz, 1986) …”
Section: Resultssupporting
confidence: 63%
“…11,[27][28][29] A survey of women with stage III breast cancer subject to the same kind of treatment showed a difference in DFS at 5 years between stage IIIA (84%) and IIIB (33%) patients. 30 In a study that compiled data from the EUROCARE and SEER trials, the risk of death was shown to increase alongside staging (T2-3N0M0: risk of 4.87; T1-3NM0: risk of 10.44; T4M0: risk of 17.22; all in relation to T1N0M0). 31 Allemani et al noted relative survival estimates of 89% for patients with tumors confined to the breast and 62% for tumors with lymph node involvement.…”
Section: Discussionmentioning
confidence: 99%
“…9). Even with neoadjuvant and multimodality treatment, disease-free survival is still poor (10,11) and there is an unmet clinical need for new therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%